Stock price synchronicity and firm's exposure to financial crisis: evidence from emerging markets - Heleka, Ashraf Abdelnasser (AUC Knowledge Fountain, 2015)
This paper uses pre-crisis stock price synchronicity to explain the cross-sectional variation in within-crisis synchronicity. Using a large dataset from 19 emerging markets, we show that firms with high pre-crisis synchronicity are affected less by financial crisis than firms with low pre-crisis synchronicity. We document an inverse parabolic relationship between pre-crisis synchronicity and within-crisis synchronicity. Our results show that the relationship between pre-crisis synchronicity and within-crisis synchronicity is positive until a turning point is reached. After that value, pre-crisis synchronicity has a negative impact on within-crisis synchronicity. We argue that firms with high pre-crisis synchronicity are, generally, associated with superior governance mechanisms (Chan and Hameed, 2006; Dasgupta et al., 2010). Better governance mechanisms lead to lower exposure of these firms to financial crisis (Mitton, 2002). Our results are also robust across different sub-samples.